RELATIONSHIP OF GROWTH HORMONE RECEPTOR GENE WITH SOME OF PRODUCTIVE TRAITS OF COMMON CARP Cyprinus carpio - Yousef T. A.,; M. S. Al-Khshali, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed of determining the relationship of polymorphism of the growth hormone receptor gene with some of growth traits (daily growth rate, relative and specific growth, ratio and efficiency of feed conversion) in 45 samples of common carp (Cyprinus carpio). The following are the most important results obtained: The results of DNA sequencing and single nucleotide polymorphism (SNP) showed there are of three mutations in the following sites C24074T, A24375G and G24485A. No genetic makeup was significantly associated with the studied growth characteristics. It is concluded from this study that there is no significant effect of the difference in the genotypes of the growth hormone receptor gene on the growth characteristics of common carp fish.